Prospects on Cattle Based Crop-Livestock Systems for The Irrigated Paddy Field in Lombok - Hasil Sembiring; Tanda Panjaitan; Mashur .; Dwi Praptomo; A Muzani; A Sauki; Wildan .; Mansyur .; Sasongko .; Nurul A (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2002)
Grouped livestock management is one of the characteristic animals raising in Lombok. In the year of 2000, there were 1096 farmers' group that had a very potential opportunity to optimize the livestock productions through the crop-livestock systems approach. The assessment of this approach for the irrigated paddy field area has being conducted in the village of Sepakok, sub- district of Pringgarata, district of Lombok Tengah. The objective of the study was to improve the efficiency and sustainability of the crop-livestock system as well as environmentally friendly issues. A total of 112 household farmers were involved in the study, joined in the "Gerak Maju" group farmer with 334 head of cattles and 35 ha paddy filed. Improving farming systems efficiency has been implemented through the technology introduction of rice straw fermentation as cattle feeds, the use of Progesterone Intravaginal Sponges (PIS) for estrous synchronization and compost processing as well as its uses for crips. The results has shown that fermented rice straw could be used as basal feed, given ad-libitum and 5% of native grass from the body weight yield an average daily gain of 290 gr. The use of fermented rice straw has decreased the straw-field in the field after harvesting period, so that it could be storage and used them for the dry season. The use of manure compost could reduce the production cost for anorganic fertilizer and weed. It significantly affected to the vegetative growth of some horticultures. Part of the compost production has been marketed in some areas to give additional income of the farmers. The crop-livestock system approach with cattle based in the irrigated paddy field was recognized as one of the potential systems that could be impemented in Lombok as well as other region with the same agro-ecological zone.   Key words: Crop-livestock systems, fermented rice straw, compost